Theoretical basis of essential-oil-bearing plants introduction (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
Theoretical foundations of essential-oil-bearing plants' introduction is established including issues of selection, study and cultivation of source material. According to the conception, introduction is based on the search of theoretically possible terpenoids among genera and species studied. Schemes-matrixes of plants' hypoteticaly possible terpenoids search are compiled using Lamiaceae and Asteraceae families as examples.
Keywords: introduction, essential-oil-bearing plants, terpenoids, еssential oil.